2021
DOI: 10.1101/2021.02.24.432707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of dsRNA delivery methods for targeting macrophage migration inhibitory factor MIF in RNAi-based aphid control

Abstract: Macrophage migration inhibitory factors (MIF) are multifunctional proteins regulating major processes in mammals, including activation of innate immune responses. In invertebrates, MIF proteins participate in the modulation of host immune responses when secreted by parasitic organisms, such as aphids. In this study, we assessed the possibility to use MIF genes as targets for RNA interference (RNAi)-based control of the grain aphid Sitobion avenae (Sa) on barley (Hordeum vulgare). When nymphs were fed on artifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…For instance, Biedenkopf et al (2020) reported efficient SIGS of the aphid ( S. avenae ) Shp gene (encoding a structural sheath protein) when applying dsRNA to detached barley leaves. However, Liu et al (2021) reported that the application of naked dsRNA on barley plants was inefficient in silencing different target genes (microphage migration inhibitory factor genes MIF1, MIF2 , and MIF3 ) in the same aphid species, even though nymphs fed an artificial diet containing this dsRNA showed efficient silencing. Furthermore, the authors were unable to detect transport of fluorescently labeled dsRNA into phloem cells, contradicting the findings of Biedenkopf et al (2020) .…”
Section: Molecular Mechanisms Underlying Higsmentioning
confidence: 99%
“…For instance, Biedenkopf et al (2020) reported efficient SIGS of the aphid ( S. avenae ) Shp gene (encoding a structural sheath protein) when applying dsRNA to detached barley leaves. However, Liu et al (2021) reported that the application of naked dsRNA on barley plants was inefficient in silencing different target genes (microphage migration inhibitory factor genes MIF1, MIF2 , and MIF3 ) in the same aphid species, even though nymphs fed an artificial diet containing this dsRNA showed efficient silencing. Furthermore, the authors were unable to detect transport of fluorescently labeled dsRNA into phloem cells, contradicting the findings of Biedenkopf et al (2020) .…”
Section: Molecular Mechanisms Underlying Higsmentioning
confidence: 99%
“…Transgenic barley plants producing double-stranded (ds)RNA exported corresponding sRNAs into the powdery mildew fungus, where they subsequently silenced target genes. Many reports have confirmed that HIGS can mediate strong resistance against target organisms including fungi, oomycetes and insects thereby demonstrating the great agronomic potential of artificial sRNAs (Knip et al 2014; Cai et al 2018b; Liu et al 2020; Šečić and Kogel 2021).…”
Section: Introductionmentioning
confidence: 98%
“…However, parasitic species have been shown to produce several MIF proteins, some of which are designated for secretion and to modulate the immune responses in the host organism thus facilitating infection (Pastrana et al, 1998; Augustijn et al, 2007; Cho et al, 2011; Miller et al, 2012; Ajonina-Ekoti et al, 2013; Naessens et al, 2015; Zhao et al, 2019). Studies on the mode of action and function of such MIF proteins have mainly been conducted on human and plant parasites such as nematodes, protozoa or aphids (Augustijn et al, 2007; Vermeire et al, 2008, Naessens et al, 2015; Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%